First record of Botryosphaeria dothidea associated with pistachio (Pistacia vera L.) panicle blight in Iran - Hamid Mohammadi; Mehdi Sarcheshmehpour; Ebrahim Mafi (Journal of Crop Protection, 2015)
During spring and summer of 2012, a disease characterized by panicle blight was observed on some pistachio (Pistacia vera L.) trees grown in Kerman province. Eighteen isolates of a Botryosphaeriaceae were obtained from affected panicles. Based on morphological and molecular characteristics, isolates were identified as Botrysphaeria dothidea. To our knowledge, this is the first report of B. dothidea associated with pistachio panicles in Iran.